SISTEM INFORMASI RESERVASI RESTORAN: (STUDI KASUS : RESTORAN OMAHKU) - Linda Apriyanti; Nurfitriyana Rizkiyah (JURTIK:Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2020)
This study discusses information systems that can facilitate customers in making reservations, namely by utilizing a web browser as a media to reserve a table. Where, customers do not have to come directly to the restaurant just to order the desired table, just by opening the website provided, customers can immediately make a reservation. The making of this system is also intended to facilitate the presentation of reports. The writing research methodology uses object-oriented methodology, with modeling tools for design using UML (Unified Modeling Language). The system development method used in this study is to use the waterfall method, which describes a systematic and sequential thing in software development. This method, starts from analyzing system requirements, namely by conducting interviews and surveys of objects. Then design the system according to the analysis that has been done before. After completing the analysis and design, the next stage is the implementation of the system that has been created, and ended by testing the functions contained in the system created. Reservation reservation table that runs before, still uses a conventional system, where customers must call or come directly to the restaurant when making a reservation. This makes customers have to spend costs and time when making direct reservations or telephones. Non-centralized reservation data also has an impact on the presentation of reports, where, when customers make reservasai, the receptionist records the reservation data on a piece of paper, so that, to present the reservation data report, it needs to be copied first. The results of making this restaurant reservation information system, are expected to be able to improve restaurant performance in service to its customers, especially services in restaurant reservation activities carried out by customers. In addition to making it easier for customers to make reservations, with this system, customers can also save costs and energy, by not coming directly or making calls to restaurants. This system is also expected to help restaurants to store restaurant reservation data centrally. And can help in the preparation of reservation data so that it becomes accurate and accurate information. Keywords: Information system restaurant reservation, UML